2019
DOI: 10.3390/nu11040907
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-Type Hypersensitivity Underlying Casein Allergy Is Suppressed by Extracellular Vesicles Carrying miRNA-150

Abstract: In patients with non-IgE-mediated milk allergy, a cellular mechanism of delayed-type hypersensitivity (DTH) is considered. Recent findings prove that cell-mediated reactions can be antigen-specifically inhibited by extracellular vesicles (EVs) carrying miRNA-150. We sought to establish a new mouse model of DTH to casein and test the possibility of antigen-specific suppression of the inflammatory reaction. To produce soluble antigenic peptides, casein was subjected to alkaline hydrolysis. DTH reaction to casein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 38 publications
2
60
0
Order By: Relevance
“…Then, Ts cell‐derived EVs carrying miRNA‐150, additionally coated with hapten‐specific LCs, were shown to suppress the hapten‐induced CHS reaction antigen‐specifically in vivo (Figure 2). 139,148 Recently, we have found that an analogous tolerance mechanism could be induced in DTH to ovalbumin and bovine casein administered without an adjuvant 150 . The antigen‐specificity of the observed mechanism of DTH suppression by miRNA‐150‐carrying EVs was proved by testing of EVs mediating tolerance to keyhole limpet haemocyanin in active, ovalbumin‐induced DTH, 151 and of ovalbumin‐specific EVs in casein‐induced DTH 150 .…”
Section: The Apc‐ev‐mirna‐150 Circuit In the Regulation Of Dth To Selmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, Ts cell‐derived EVs carrying miRNA‐150, additionally coated with hapten‐specific LCs, were shown to suppress the hapten‐induced CHS reaction antigen‐specifically in vivo (Figure 2). 139,148 Recently, we have found that an analogous tolerance mechanism could be induced in DTH to ovalbumin and bovine casein administered without an adjuvant 150 . The antigen‐specificity of the observed mechanism of DTH suppression by miRNA‐150‐carrying EVs was proved by testing of EVs mediating tolerance to keyhole limpet haemocyanin in active, ovalbumin‐induced DTH, 151 and of ovalbumin‐specific EVs in casein‐induced DTH 150 .…”
Section: The Apc‐ev‐mirna‐150 Circuit In the Regulation Of Dth To Selmentioning
confidence: 99%
“… 139,148 Recently, we have found that an analogous tolerance mechanism could be induced in DTH to ovalbumin and bovine casein administered without an adjuvant 150 . The antigen‐specificity of the observed mechanism of DTH suppression by miRNA‐150‐carrying EVs was proved by testing of EVs mediating tolerance to keyhole limpet haemocyanin in active, ovalbumin‐induced DTH, 151 and of ovalbumin‐specific EVs in casein‐induced DTH 150 . Interestingly, suppressed DTH reaction was observed in mice treated with Ts cell‐derived EVs administered via intraperitoneal, intravenous, intradermal or even oral routes 150 .…”
Section: The Apc‐ev‐mirna‐150 Circuit In the Regulation Of Dth To Selmentioning
confidence: 99%
See 1 more Smart Citation
“…Most food allergies manifest in two general forms based on the time of appearance of clinical symptoms after exposure and the underlying immune mechanisms involved in eliciting them [3,4,82]. They are: (i) immediate (or Type I or IgE antibody-mediated) hypersensitivity reactions, where symptoms appear within minutes to 3 h; and (ii) delayed (or Type IV or cell mediated) hypersensitivity reactions, where symptoms of reaction appear after 48-72 h of exposure to the food allergens [83,84]. Most food allergies are of the Type I nature.…”
Section: Pathogenesis Of Sesame Allergy: Gaps In the Cellular And Molmentioning
confidence: 99%
“…Most food allergies are of the Type I nature. However, some food allergies such as milk allergies can involve both Type I and Type IV reactions [84].…”
Section: Pathogenesis Of Sesame Allergy: Gaps In the Cellular And Molmentioning
confidence: 99%